Emerging trends in the international exchange of plant genetic resources for food and agriculture: Cross-country evidence on the effects of the 2014 Nagoya Protocol - Takeshima, Hiroyuki; Mekonnen, Dawit Kelemework; Spielman, David J. (International Food Policy Research Institute, 2024)
Presentation given at the Annual Meeting of the NC 1034 Multistate Research Group on “Impact Analysis and Decision Strategies for Agricultural Research” Colorado State University, Fort Collins, CO, March 29-30, 2024.